Fueling immunity: the synergy of natural products and exercise for optimal health - Fuzhen Li; Wei Zhou; Jun Wang (Frontiers in Pharmacology)
Moderate exercise has been associated with improved immune function and a reduced risk of inflammatory conditions and infections. Some evidence also suggests a potential role in reducing cancer risk. In contrast, excessive physical activity can suppress the immune system and increase the risk of inflammatory and allergic conditions. The vulnerability to infections associated with overexertion is linked to elevated levels of immunosuppressive factors, such as adrenocortical hormones and anti-inflammatory cytokines. These changes reduce the number and activity of natural killer (NK) cells and T cells and decrease IgA levels in saliva. Consequently, athletes engaged in high-intensity training may face a greater risk of compromised immune function. In the sports nutrition market, a range of natural products is available, but many lack clear evidence of effectiveness and are marketed with misleading claims, leading to consumer confusion. The efficacy of food components discussed in this article warrants further investigation due to differing opinions in research. Additionally, the effectiveness of these components may vary by gender, differences, and method of consumption. Therefore, future research is needed to determine optimal intake methods and timing of these products based on their intended use and physiological changes resulting from exercise. This review explores the effects of natural products combined with exercise on maintenance and reduction.